Ambulance emergency responses vulnerability analysis towards traffic conditions using GIS / Nur Amirah Suhaimi and Nabilah Naharudin - Suhaimi, Nur Amirah; Naharudin, Nabilah (2023)
Rising incidents of emergency responses late arrival at the crime scenes due to the issue of increasing traffic volumes day by day has becoming one of the concerns in KL City Centre. The traffic congestion could hinder emergency responses that need to reach the accident location within stipulated time. The purpose of this study is to analyse the vulnerability of ambulance emergency responses towards traffic conditions using GIS. In this study, the Ambulance Responses Traffic Vulnerability (ARTV) Index is introduced to measure the variability in ambulance responses performance due to traffic vulnerability in each region since KL City Centre is an urban area where traffic-congested happened every day. The ARTV index is unitless, and a higher ARTV indicates that the area is more vulnerable to traffic conditions and travel time uncertainty, whereas a lower ARTV indicates that the area is less vulnerable to traffic conditions and travel time uncertainty. By computing the value of this ARTV Index, it is possible to determine which locations are least vulnerable, intermediately vulnerable, vulnerable, and most sensitive to traffic conditions, particularly during peak and off-peak hours. Based on the finding, the central part of KL City Centre has high ARTV index indicating the ambulance responses tend to be vulnerable towards the traffic condition, thus the responses time may be slower when the traffic congestion is high. The ARTV index was visualized as a map which is expected to be useful as a guidance in improving the emergency responses in KL City Centre.